Agricultural Crisis Mitigation Strategy through Scientific Interpretation: A Study on Tafsir Ilmi by the Indonesian Ministry of Religious Affairs - Fajariyah, Lukman; Masuwd, Mowafg Abrahem (Institut Agama Islam Negeri (IAIN) Keiri, 2024)
This research examines the scientific interpretation of agricultural verses in the Ministry of Religion’s interpretation. The Ministry of Religion’s scientific interpretation work responds to efforts to integrate science and the Qur’an. It is motivated by modern social life characterized by advances in science and technology. Scientific interpretation is used in interpreting kauniyah verses by involving scientific tools. The meaning revealed results from a dialectical process between the Qur’an and scientific disciplines or modern science. This qualitative-descriptive research seeks to trace and classify the interpretation of agricultural verses in the Ministry of Religion’s scientific interpretation works. The findings show that the Ministry of Religion’s scientific interpretation of agricultural verses includes several aspects, such as the nature of human creation as managers of the earth, livelihoods, land use, use of plants for human life, water resources, and preventing water crises. The Ministry of Religion’s scientific interpretation of these agricultural verses responds to contemporary environmental crises and global warming phenomena. This interpretation also provides insight into ecological preservation by farming as a provider of life in the universe. Such environmental preservation can mitigate global crises caused by rapid industrial and technological life.